KOMUNIKASI PEMASARAN TERPADU MAKE OVER MELALUI BEAUTY VLOGGER DALAM MEMBANGUN CITRA MEREK - Farras Zahra (Universitas Serang Raya, 2017)
This research was a case where researchers curiosity to know the use of integrated marketing komunuikasi using beauty vlogger role of sarah ayu in building brand product image makeover .This research use descriptive methods with techniques qualitative data collection of in-depth interviews , and the study of literature .This research concluded that with integrated marketing communications by sarah ayu as beauty vlogger can build a brand image make overs become better with video shown by sarah ayu where in the video explains sarah ayu one by one the quality of the product that has been used in the video .With explanations of those products make the audience gave positive responses against brand make overs .Attitude with communication resulting from watching the video is brand image makeover namely positive image in view of the consumer .